The Role of Hanacaraka Wonogiri Islamic Boarding School in Empowering The Community to Preserve Javanese Culture - Wakit Wakit; Mibtadin Mibtadin; Prasetyo Adi Wisnu Wibowo (Javanologi: International Journal of Javanese Studies, 2024)
The existence of Islamic boarding schools in society is not only an Islamic educational institution but also develops local Pesantren culture as an effort to develop society and maintain the preservation of Javanese culture. What are the efforts of the Hanacaraka Islamic Boarding School in empowering the community to preserve Javanese culture? This research is descriptive qualitative; data collection was carried out through observation, deep interviews, and documentation about the religious education of the Hanacaraka Islamic Boarding School. Data analysis uses an interactive analysis model: data reduction, data delivery, and conclusion drawing. Hanacaraka Islamic Boarding School is a modern Javanese cultural-style Islamic boarding school founded in Wonogiri in 2010. The Hanacaraka Islamic Boarding School aims to preserve Javanese culture and local wisdom, strengthening Islamic and Indonesian discourse. Hanacaraka Islamic Boarding School, as a center for community empowerment, is a driving force for social, cultural, and religious change. The character of the Hanacaraka Islamic Boarding School, which is integrated with society, becomes a cultural and Islamic filter for developments in the world outside itself. The Hanacaraka Islamic Boarding School carries out two mandates, al-amanah al-diniyah, and al-amanah al-tsaqofah, so there is no conflict between religion and culture. The distinctive character of the Hanacaraka Islamic Boarding School, which is based on Javanese culture, provides an important understanding for the community that Islam and Javanese culture do not have to be confronted. Religion and culture are like two sides of a coin that strengthen each other. Religion is a source of values, soul, and spirit, while Javanese culture provides a forum for developing these values. Hanacaraka Islamic Boarding School is a washilah for passing on Javanese culture to the millennial generation and society in general through training in Javanese gamelan, puppetry, and forming Mandraguna klenengan. Apart from that, Javanese culture is also used as nadhoman to carry out Islamic da'wah through songs and gamelan. Formal education through a local content curriculum is routinely carried out by the Hanacaraka Islamic Boarding School community and students, practicing Javanese culture such as gamelan, klenengan, wayangan, and Javanese syi'iran. Meanwhile, through non-formal education, preserving Javanese culture using Javanese poetry or songs containing direct religious teachings maintains culture so it does not become timeless.